A study of the undrained shear strength of soft clay reinforced with 10mm and 16mm diameter single encapsulated bottom ash column - Suzillco , Suki (2015)
Stone column is one of the most commonly used in soil improvement technique around the world which capable to increase the bearing capacity of soft clay and able to reduce the settlement of superstructure constructed on them. Due to its higher value of strength and stiffness, it can sustain larger proportion of the applied load which improves the performance of foundation beds. Meanwhile, the substantial amount of bottom ash disposed in the landfills have causes a serious environment pollution. As the bottom ash is part of the residue of combustion of coal and also the by-product produced in a furnace of the power plant. Hence, by reutilize the bottom ash as granular material in vertical granular column, the cost of construction can be reduced and able to achieve more strength of soft clay after being reinforced with a single bottom ash column which been encased with geotextile. The first stage of the study was determine the physical and mechanical properties of the material used such as soft clay and bottom ash. The results shows that kaolin can be classified as silty soil while the properties of bottom ash has relatively similar characteristic with sand. At the second stage, remoulded specimens of 50mm in diameter and 100mm in height soft kaolin clay with single encapsulated bottom ash columns was subsequently tested under Unconfined Compression Test. The diameter of the encapsulated bottom ash column is 10mm and 16mm. It can be concluded that the shear strength parameters shows some significant improvement on encased and non-encased bottom ash columns and were affected by the diameter and height of the column.